Bone Cut Accuracy in Total Knee Arthroplasty: Do Conventional Cutting Guides Stay True to the Planned Coronal Orientation of the Components? - Joan Leal-Blanquet; Pedro Hinarejos; Elisenda Gimenez-Valero; Raul Torres-Claramunt; Juan Sánchez-Soler; Juan Erquicia; Sergi Gil-González; Angela Zumel-Marne; Juan Carlos Monllau (Applied Sciences, 2023)
Background: Total knee arthroplasty (TKA) has become the gold standard for the definitive treatment of knee osteoarthritis. One crucial aspect in the implantation of a TKA is the precise orientation of the femoral and tibial components. The main purpose of the present study is to assess, in patients undergoing total knee replacement, whether the difference between the planned angulation in the distal femoral cut and the angulation obtained in the postoperative radiological control is low enough to consider the conventional bone-cutting guides reliable. Methods: A retrospective study was designed with a consecutive series of patients who had undergone primary total knee arthroplasty using conventional instrumentation over one year. The authors analysed the main variable (bone cuts) while considering different variables (age, gender, surgeon, prosthesis, laterality, constraint, body mass index and alignment) to identify different patient patterns that justify the results in the main variable. Descriptive variables were analysed using the Mann–Whitney U and Kruskal–Wallis tests. Additionally, the correlation between continuous variables was explored in accordance with the Spearman correlation. Results: A total of 340 patients with a mean age of 75 ± 9.16 years were finally included in the present study. The mean absolute error of the main variable for the femoral coronal bone cut was 1.89° (SD 1.53). For the tibial coronal bone cut, it was 1.31° (SD 2.54). These values correspond to what remains after subtracting the radiological angulation obtained in the postoperative period from the planned intraoperative angulation of the distal femoral cut. No associations were observed between the main variable (the angulation of the proximal tibial cut and distal femoral cut) and the rest of variables for either the femur or tibia. Conclusion: A discrepancy between the planned angulation and the final radiological measure on the coronal plane of the femur and tibia using conventional cutting guides has been demonstrated. The degree of deviation is low enough that it probably does not affect clinical outcomes. Therefore, the use of conventional cutting guides will continue to be an appropriate tool to perform bone cuts in knee replacement surgery.